Fatal Clostridium perfringens sepsis with spleen rupture and intraabdominal massive bleeding in a 37-week pregnancy. (2021) - Gafumbegete, Evariste; van der Weide, Berend Jacob; Misgeld, Stefanie; Schmidt, Henning; Elsharkawy, Alaa Eldin
Abstract: The maternal death rate remains unacceptably high worldwide, predominantly in areas of poor access to quality health services. According to the WHO, in 2017, 810 women died from preventable causes related to pregnancy and childbirth. Causes of maternal death are plenty, including previous morbidity and unexpected causes. Among the latter are infectious disease-related deaths. Herein, we describe a case of a 29-year-old woman at 37 weeks' gestation who presented with right upper quadrant pain, which was initially considered to be pregnancy-related. However, she collapsed shortly after the hospital admission. The physical examination revealed severe hypovolemic shock due to a large amount of intraperitoneal free fluid. The patient was immediately rushed into an emergency cesarean section followed by exploratory laparotomy, which demonstrated a large intra-abdominal hemorrhage. The patient and her fetus died in the operating room. An autopsy revealed acute gangrenous cholecystitis along with abundant rod-shaped bacteria within the mucosa and vessels of the gallbladder, gas gangrene and rupture of the spleen, and signs of shock. Clostridium perfringens (CP) was isolated in the culture of a splenic sample. Although CP is a well-known and dreadful infectious etiological agent, catastrophic cases still happen. The acquaintance of this infection by the caregivers is crucial for the early diagnosis and treatment. This is a quite unique way to provide a dismal chance of survival in sepsis cases by this agent.